How Expensive is the Welfare State? Gross and Net Indicators in the OECD Social Expenditure Database (SOCX) - Adema, Willem (OECD Social, Employment and Migration Working Papers, 2009)
This paper first presents information on trends and composition of social expenditure across the OECD. Gross public social expenditure on average across OECD increased from 16% of GDP in 1980 to 21% in 2005, of which public pensions (7% of GDP) and public health expenditure (6% of GDP) are the largest items. This paper then accounts for the effects of the tax system and private social expenditure which leads to a greater similarity in social expenditure-to-GDP ratios across countries and to a reassessment of the magnitude of welfare states. After accounting for the impact of taxation and private benefits, social expenditure (1) amounts to over 30% of GDP at factor cost in Belgium, Germany, and France and (2) ranges within a few percentage points of each other in Austria, Canada, Denmark, Finland, Italy, the Netherlands, Portugal and the United States